Mathematical Critical Thinking Ability in DAPIC Problem Solving Learning with Scientific-RME Approach in Students Learning Independent (Unnes Journal of Mathematics Education, 2022)
Mathematical critical thinking ability is an ability that students in learning mathematics must possess. The purpose of this study was to analyze critical thinking ability reviewed from independence tend and to describe students’ critical thinking ability on DAPIC Problem Solving in independence tend. The population in the study were all students of class VIII Junior High School 43 Semarang Year 2020/2021. The research method used was a mixed method with a sequential explanatory design. Research results showed that: (1) students' mathematical critical thinking skills in DAPIC Problem Solving learning with the Scientific-RME approach could achieve minimum completeness criteria; (2) students' mathematical critical thinking skills in DAPIC Problem Solving learning with the Scientific-RME approach achieved classical learning completeness; (3) average critical thinking ability in the DAPIC Problem Solving learning with the Scientific-RME approach more than from Problem Based Learning; (4) proportion result test critical thinking ability in the DAPIC Problem Solving learning approach Scientific-RME is better than Problem Based Learning; (5) critical thinking ability with five indicators think critical is in the subject category high, moderate, and low learning independence tend.